Swedish Healthcare Direct managers’ views on gender (in)equity: applying a conceptual model - Kaminsky, Elenor; Höglund, Anna T. (International journal for equity in health, 2019)
Although Swedish legislation prescribes equity in healthcare, inequitable healthcare is repeatedly reported in Sweden. Telephone nursing is suggested to promote equitable healthcare, making it just one call away for anyone, at any time, irrespective of distance. However, paediatric health calls reflect that male parents are referred to other health services twice as much as female parents are. Regarding equity in healthcare, telephone nurses have expressed a continuum from Denial and Defence to Openness and Awareness. To make a change, Action is also needed, within organizational frames. The aim here was thus to investigate Swedish Healthcare Direct managers' views on gender (in)equity in healthcare through the application of a conceptual model, developed based on empirical Swedish Healthcare Direct telephone RN data, as a baseline measure at the service's national implementation. All Swedish Healthcare Direct managers were interviewed during the period March-May 2012. They were asked how they view equitable healthcare, and how they work to achieve it. A conceptual model for attaining equity in healthcare, including Denial, Defence, Openness, Awareness and Action, was used in a deductive thematic analysis of the interview data. The five model concepts - Denial; Defence; Openness; Awareness and Action - were found in a variety of combinations in the manager interviews. Denial and Defence were mentioned to a higher extent than Openness and Awareness. Several informants denied inequity, arguing that the decision support tool prevented this. However, those who primarily expressed Denial and Defence were also open to learning more on the subject. Action was only mentioned twice in the informants' answers, and then only implicitly. Although a majority of the interviewed managers expressed a lack of awareness of (in)equity in healthcare, they also expressed an openness to learning more. While this may reflect a desire to show political correctness, it also points to the need for educational training in order to increase the awareness of (in)equity in healthcare among healthcare managers. Future follow up measurements will reveal if this has happened.